1994
DOI: 10.1073/pnas.91.22.10260
|View full text |Cite
|
Sign up to set email alerts
|

A truncated bone morphogenetic protein 4 receptor alters the fate of ventral mesoderm to dorsal mesoderm: roles of animal pole tissue in the development of ventral mesoderm.

Abstract: The biological effects of endogenous bone morphogenetic protein 4 (BMP-4), a member of the transforming growth factor 13 family, on embryonic development of Xenopus laevis were investigated by using a functionally defective mutant of the BMP-4 receptor (AmTFR11)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(74 citation statements)
references
References 28 publications
5
69
0
Order By: Relevance
“…To elucidate the involvement of BMPR-IA in the BMP-2 signaling in C2C12 cells, a kinase domain-truncated BMPR-IA was constructed and stably transfected into C2C12 cells. This truncated BMPR-IA acts as a dominant negative receptor for BMP-4 signaling in the Xenopus embryo (23,34,35). When the kinase domain-truncated BMPR-IA was overexpressed in C2C12 myoblasts, they differentiated into MHC-positive myotubes but not into osteoblastlike ALP-positive cells, even in the presence of BMP-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the involvement of BMPR-IA in the BMP-2 signaling in C2C12 cells, a kinase domain-truncated BMPR-IA was constructed and stably transfected into C2C12 cells. This truncated BMPR-IA acts as a dominant negative receptor for BMP-4 signaling in the Xenopus embryo (23,34,35). When the kinase domain-truncated BMPR-IA was overexpressed in C2C12 myoblasts, they differentiated into MHC-positive myotubes but not into osteoblastlike ALP-positive cells, even in the presence of BMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…A kinase domain-truncated BMPR-IA abolished the ventralizing activity of BMP-4 in a dominant negative manner in the Xenopus embryo (23,34,35). We therefore examined whether a dominant negative BMP type I receptor could inhibit the BMP-2-induced signalings in myoblasts.…”
mentioning
confidence: 99%
“…In addition to a modulation of Wnt signals, differentiation of lateral plate mesoderm into either an anterior (i.e., heart) or posterior (i.e., blood) cell fate requires concomitant BMP signaling (Dale et al 1992;Jones et al 1992;Fainsod et al 1994;Graff et al 1994;Maeno et al 1994;Suzuki et al 1994;Andreé et al 1998;Schlange et al 2000), which is present only in the lateral (ventral) domains of the embryo. Thus, mesoderm located in regions of the gastrula stage embryo that are exposed to low levels of Wnt signaling and high levels of BMP signals develop into cardiac tissue (illustrated in Fig.…”
Section: Wnt Inhibition Promotes Heart Muscle Formation From Posteriomentioning
confidence: 99%
“…Thus, we are now examining the expression pattern of the genes encoding the above-mentioned secretory proteins and planning to examine the effect of these secretory proteins on the flounder-specific adult pigment pattern. Because it has been reported that the signaling by these secretory proteins is involved in embryonic dorsoventral axis formation (Smith et al, 1993;Graff et al, 1994;Maeno et al, 1994;Suzuki et al, 1994;Funayama et al, 1995;He et al, 1995;Schneider et al, 1996;Sokol, 1996;Sumoy et al, 1999;Cho et al, 2006), we are very interested in whether these proteins may relate to the conversion from left-right axis to dorsalventral axis in flatfish during the process of metamorphosis.…”
Section: Japanese Flounder Adulttype Pigment Cells Are Derived From Dmentioning
confidence: 99%